MENGEMBANGKAN BUDAYA DAMAI DI SEKOLAH MELALUI MANAJEMEN KELAS YANG DEMOKRATIS BERBASIS NILAI-NILAI KEISLAMAN - Ahmad, Askar (Institut Agama Islam Negeri (IAIN) Palu, 2009)
Islam is a religion of peace. Therefore, Islam accommodates differences in religions, ethnics, languages, and cultures. Islam also recommends that peace culture be established at any time and place. One of the places where peace culture can be established is through classÂ management at schools.Â Based on this, class should be managed by employing socio-emotional principles such as Â mutual appreciating, mutual understanding, and mutual respecting, both between students and students and students and teachers.Kata Kunci: budaya damai, konflik, sekolah, manajeman kelas